Pengaruh Marketing Mix (Product, Place, Promotion, Price, People) Terhadap Minat Berkunjung Masyarakat ke Poli Anak Rumah Sakit Islam Hasanah Muhammadiyah Mojokerto - Pestaria Sianipar; Wani Devita Gunardi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Good hospital service is crucial because patients' perceptions of service quality are formed during their visit to a healthcare institution. The marketing mix is the most visible (tangible) component of a company's marketing activities, making it crucial because companies must create attractive offers and consider appropriate distribution and promotion tactics. The purpose of this study was to examine the influence of the marketing mix (product, place, promotion, price, people) on public intention to visit the Children's Clinic at Hasanah Muhammadiyah Islamic Hospital, Mojokerto. The study sample was taken from 80 respondents at the Children's Clinic at Hasanah Muhammadiyah Islamic Hospital, Mojokerto. Data were obtained through questionnaires, and the analysis used was multiple linear regression. The results of the analysis obtained that: 1) The product variable (X1) partially has a significant effect on the interest of the community visiting the Children's Polyclinic of RSIH Muhammadiyah Mojokerto (0.026 < 0.05). 2) The location variable (X2) partially has a significant effect on the interest of the community visiting the Children's Polyclinic of RSIH Muhammadiyah Mojokerto (0.004 < 0.05). 3) The promotion variable (X3) partially has a significant effect on the interest of the community visiting the Children's Polyclinic of RSIH Muhammadiyah Mojokerto (0.006 < 0.05). 4) The price variable (X4) partially has a significant effect on the interest of the community visiting the Children's Polyclinic of RSIH Muhammadiyah Mojokerto (0.001 < 0.05). 5) The employee variable (X5) partially has a significant effect on the interest of the community visiting the Children's Polyclinic of RSIH Muhammadiyah Mojokerto (0.003 < 0.05). 5) The variables product (X1), place (X2), promotion (X3), price (X4), and people (X5) simultaneously significantly influence public interest in visiting the Pediatric Clinic of RSIH Muhammadiyah Mojokerto (0.000 < 0.05). To increase public interest in visiting, the hospital needs to pay attention to the marketing mix and demonstrate concern for patients in need of healthcare services, provide personalized attention to each individual, and remind patients of medical recommendations to follow. The hospital is expected to continue providing professional services to both BPJS patients and the general public so that the public maintains trust in the hospital's services.